The directive function of the English modals - Butler, Christopher (1982)
The aim of this thesis is to provide a detailed account, within a 'systemic' framework of those properties of English sentences containing modal verbs, which will allow us to make predictions about the potential directiveness of some such sentences but not others, about ambiguity of communicative function, and about certain social properties of directives.